2016
DOI: 10.1242/dev.130773
|View full text |Cite
|
Sign up to set email alerts
|

SUMO regulates somatic cyst stem cells maintenance and directly targets hedgehog pathway in adult Drosophila testis

Abstract: SUMO (Small ubiquitin-related modifier) modification (SUMOylation) is a highly dynamic post-translational modification (PTM) that plays important roles in tissue development and disease progression. However, its function in adult stem cell maintenance is largely unknown. Here, we report the function of SUMOylation in somatic cyst stem cell (CySC) self-renewal in adult Drosophila testis. The SUMO pathway cell-autonomously regulates CySC maintenance. Reduction of SUMOylation promotes premature differentiation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 52 publications
(58 reference statements)
1
22
0
Order By: Relevance
“…The role of Ubc9 in regulating stem cells depends on the context and the experimental models in which the studies are performed [42][43][44][45]. For example, Ubc9 function is required for embryonic stem cell survival in vitro and reprogramming of induced pluripotent cells (iPS) but Ubc9 function is not pertinent to the maintenance of mouse embryonic fibroblasts (MEFs) [46].…”
Section: Discussionmentioning
confidence: 99%
“…The role of Ubc9 in regulating stem cells depends on the context and the experimental models in which the studies are performed [42][43][44][45]. For example, Ubc9 function is required for embryonic stem cell survival in vitro and reprogramming of induced pluripotent cells (iPS) but Ubc9 function is not pertinent to the maintenance of mouse embryonic fibroblasts (MEFs) [46].…”
Section: Discussionmentioning
confidence: 99%
“…In one report, forced expression of the putative Gli SUMOylation E3 ligase PIAS1 in chicken embryos was shown to increase Gli activity and cause ectopic expression of a Gli target gene in the neural tube (42). This positive role was corroborated in a separate study that showed that mutating 10 lysine residues of possible SUMOylation sites in Ci abolished the transcriptional activity of the mutant Ci in the Drosophila testis (44). However, another report showed that mutating Gli2 SUMOylation sites significantly increased Gli2 transcriptional activity both in a cell-based assay and in mice, possibly because these sites were also shown to be required for recruiting the histone modifier HDAC5, which represses transcription (43).…”
Section: Discussionmentioning
confidence: 85%
“…Several recent studies showing SUMOylation of Gli proteins have been reported (42)(43)(44), revealing that all 3 Gli proteins are modified at several phylogenetically conserved sites encompassing the consensus sequence ⌿KXE, but these studies diverge on the role of this modification in Shh signaling. In one report, forced expression of the putative Gli SUMOylation E3 ligase PIAS1 in chicken embryos was shown to increase Gli activity and cause ectopic expression of a Gli target gene in the neural tube (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations